Addressing Barriers to entry into international trade by SMEs in Zimbabwe - Mashizha, Margaret; Gumbo, Lillian; Chimwe, Eusebia (goodwood publishing, 2023)
Purpose: The study sought to establish strategies to address barriers to entry into international trade by SMEs in Harare. It was triggered by the need to increase the participation of Zimbabwean SMEs in foreign markets. Research methodology: The research study adopted an explanatory approach using a survey strategy and data was collected from 322 registered SMEs in Harare using questionnaires. Data was analysed using SPSS 27 to calculate descriptive and inferential statistics and Chi-square tests, correlation, and regression analyses were used to address the research questions. Results: Barriers to entry into international trade identified were a lack of managerial expertise and entrepreneurial skills and low advertising levels. The study recommends that SMEs increase the number of skilled personnel and develop SME management. SME management should also increase market knowledge and promote innovation to allow for SMEs to participate meaningfully in international trade. Limitation: The study was limited to SMEs operating in Harare only. It was quantitative and explanatory. Contribution: The study makes a significant contribution to the existing body of knowledge by bringing to the fore strategies that could enhance the international participation of SMEs, which are the backbone of economic growth in Zimbabwe.